Creative Problem-Solving Skills in Learning with STEM Approach - Handayani, Nadira; Noer, Sri Hastuti; Suryadinata, Nurain (PRISMA, 2025)
This study aims to determine the improvement of students' creative mathematical problem-solving skills in learning with the STEM approach. The population in this study were all VIII grade students of SMP Negeri 1 Bandar Lampung in the 2024/2025 academic year, and as many as 352 students were distributed in eleven classes. The samples of this study were classes VIII.7 and VIII.9, which were selected using a purposive sampling technique, and the research design used was a non-equivalent control group design. The data in this study are quantitative data obtained through tests to measure mathematical creative problem-solving skills. The data on the improvement score (N-Gain) in the experimental class was not normally distributed, so the data analysis in this study used the Mann-Whitney U test and the proportion test. Based on the results of the Mann-Whitney U test analysis, it was found that the increase in the mathematical creative problem-solving skills of students with the STEM approach was higher than the increase in the mathematical creative problem-solving skills of students in the conventional learning and the proportion of students who had well categorized mathematical creative problem-solving skills was more than 60% of the number of students with the STEM approach. Thus, the application of learning with the STEM approach is practical regarding the creative mathematical problem-solving skills of class VIII students at SMP Negeri 1 Bandar Lampung.